New Research on Veterans Treatment Courts: An Overview of the Community Participatory Research on Veterans in Specialized Programming Project - Byrne, James M. (Victims & offenders, 2024)
Justice-involved veterans return to civilian life with a variety of mental and physical health challenges that often go untreated and increase their risk for self-harm and involvement in the criminal-legal system. Veterans Treatment Courts (VTC) were created to respond to the unique problems of justice-involved veterans by attempting to coordinate services and support with the U.S. Department of Veterans Affairs (VA), local treatment providers, and the VTC. Our research has two distinct phases. In Phase 1, we conducted qualitative interviews with VTC team members in twenty (20) VTCs from each USA region; in each VTC, we gained the perspectives of team members – judges, prosecutors, defense attorneys, VJOs, VTC program coordinators, mentors, probation officers, and treatment providers – on the operation of VTCs, with a focus on how to improve service provision for justice-involved veterans. A total of 145 interviews were conducted. We begin by describing the unique problems and treatment needs of justice-involved veterans, and briefly summarize the findings from previous research on the implementation and impact of VTCs. We then present our research study protocol and highlight findings from our phase 1 qualitative interviews with VTC team members. In addition, we describe phase 2 of our project, which will include focus groups with VTC graduates, and quantitative analyses of the service provision networks of three VTCs.